Comments on “Fractional LMS algorithm” - Bershad, Neil J.; Wen, Fuxi; So, Hing Cheung (Signal processing, 2017)
The purpose of this note is to point out that the recently proposed fractional least mean squares (FLMS) algorithm, whose derivation is based on fractional derivative, is not suitable for adaptive signal processing. Our claims are verified via extensive simulation results with comparison with the least mean squares (LMS) algorithm, indicating that the new method does not have any advantages over the classical one.